HOW INFORMATION AND DISINFORMATION IN SOCIAL MEDIA AFFECTS NEUROLOGISTS’ MEDICAL PRESCRIPTIONS - Barreto, Amilcar (Health and Society, 2024)
Neurologists must critically evaluate social media information, due to the possibility of misinformation influencing their prescriptions. Misinformation on these platforms may mislead patients into seeking unproven treatments. Neurologists should educate their patients about the prevalence of inaccurate information online and promote the use of credible health websites. They must also stay updated with recent research, establish guidelines for discussing internet research with patients, and collaborate with human-computer interaction professionals for better results. A cautious approach towards social media can ensure accurate prescriptions and mitigate potential harm to patient care.